Synergistic enriched compost with biochar and fly ash for improving Ultisols in tropical acid soils - Shintarika, Feni; Agusta, Herdhata; Santosa, Edi; Limin, Atfritedy; Angkat, Abdul Roni; Kurniati, Kurniati (Journal of Degraded and Mining Lands Management, 2026)
Ultisols are characterized by low pH, low alkaline saturation, low cation exchange capacity, and high levels of soluble Al and Fe. Compost is usually applied to increase soil fertility, but its effect is only temporary in tropical conditions because organic matter decomposes quickly. Biochar and fly ash-enriched compost have been proposed as a synergistic approach to improve the chemical properties of Ultisols. This study evaluated the effect of compost enriched with biochar and fly ash on soil chemical dynamics over 16 months in pineapple plantations in Lampung, using a randomized block design with three treatments: compost enriched at the initial stage, compost alone as a control, and compost enriched at the end of composting. The results showed that biochar and fly ash increased soil pH during the initial phase by supplying alkaline cations. Fluctuations occurred during the intermediate stage due to the decomposition of organic matter and nitrogen transformation: organic C and total N increase, influenced by microbial activity and environmental conditions. Phosphorus followed a mineralization-immobilization-remobilization pattern, with late-stage enrichment producing P. Potassium, calcium, and magnesium initially increased but later decreased, likely due to leaching. Early-stage enrichment provided a more stable release of alkaline cations. Fe, Mn, Cu, and Zn show fluctuations in the enriched treatment. The application of biochar and fly ash-enriched compost synergistically with early-stage enrichment effectively enhances the chemical properties of Ultisol.